A pilot registry of trauma surgeons willing and ready to respond to disasters. Issue 2 (February 2018) - Grabo, Daniel; Strumwasser, Aaron; Remick, Kyle; Briggs, Susan
Abstract : BACKGROUND: A well-defined means of organizing surgeons based on functional capabilities in disaster response has been lacking. We sought to create a pilot registry of surgeons, organized by functional capacities, available to respond to disasters in conjunction with the American College of Surgeons Operation Giving Back and to better understand their participation in disaster medicine training. METHODS: The authors conducted a survey of the members of the American Association for the Surgery of Trauma and the Eastern Association for the Surgery of Trauma aimed at establishing a pilot registry of qualified trauma surgeons available to respond to disasters. Data from the surveys were analyzed retrospectively for surgical and subspecialty training, board certification, disaster response training, and military or civilian disaster experience to better understand the respondents' functional capacities and disaster training backgrounds. RESULTS: Of 211 respondents, 96% self-identified as trauma surgeons, whereas 87% and 89% reported active practice in acute care surgery and/or critical care. Nearly all had primary board certifications in general surgery (93%), and many had additional certifications in surgical critical care (65%). While many reported participation in American College of Surgeons–sponsored trauma courses, only 30% of those surveyed received disaster-specific training in Federal Emergency Management Agency courses, and even fewer received training in the Disaster Management and Emergency Preparedness course. Few had military (26%) or civilian (19%) experience in disaster response. CONCLUSIONS: This initiative complements efforts to organize a registry of trauma surgeons who are qualified and willing to respond in all aspects of disaster response. While trauma surgeons are optimally positioned to provide a wide range of surgical expertise in a disaster, this study further demonstrated the lack of a universally accepted disaster training program for surgeons willing to respond to mass casualty incidents. Standardized disaster response training for surgeons remains a challenge for the future. LEVEL OF EVIDENCE: Care management, level IV.